(untitled) (Research, Society and Development, 2024)
Alcohol, being the most widely consumed psychoactive substance globally, poses a public health problem in Brazil, with high rates of alcoholism. This study assessed alcohol consumption among 243 medical students at a private college in Minas Gerais, using the AUDIT (Alcohol Use Disorders Identification Test). Participants were classified into four risk zones based on their total AUDIT scores. Results showed that 40,7% of the students consumed alcohol regularly, while 24,3% drank occasionally. Women scored lower on the AUDIT compared to men, indicating lower consumption. Age and academic period influenced drinking patterns, with older students and those in more advanced stages of their studies consuming less alcohol. There was also a correlation between income and alcohol consumption, with higher-income students having a greater risk of dependency. Cigarette use was associated with harmful alcohol consumption, while students who preferred wine exhibited more moderate drinking habits. The study concluded that factors such as gender, academic stage, income, and smoking habits influence alcohol consumption among Medical students.